Evaluación del proceso para la obtención de CBE, mediante interesterificación enzima de una mezcla grasa a nivel laboratorio en Sigra S.A. (2018)
At present, there is no experimental evaluation in order to evaluate the process of obtaining a Cocoa Butter Equivalent (CBE) in the company. Sigra: Similar skills to Stearic Acid and Palm Olein were used for the development of this project, for which a comparison was made between the mixture of fats obtained and a reference cocoa butter, as well as the analysis of the behavior of the variables of reaction with respect to the triglycerides of interest (POP, POS and SOS). To achieve the objectives with a complete research based on articles, theses and tests in different scientific pages such as Spacenet, Springer,Elsevier and Ebsco , specifically focused on the process of obtaining CBE involving palm olein and stearic acid. With the information found, it is developed in three preliminary trials where the variables are involved (temperature, relation, agitation, reaction time and percentage of enzyme) in order to determine the level of the best working conditions in the execution of the first experiments